2009
DOI: 10.1016/j.stem.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Inhibitor of Tgf-β Signaling Replaces Sox2 in Reprogramming by Inducing Nanog

Abstract: Summary The combined activity of three transcription factors can reprogram adult cells into induced pluripotent stem (iPS) cells. However, the transgenic methods used to deliver reprogramming factors have raised concerns regarding the future utility of the resulting stem cells. These uncertainties could be overcome if each transgenic factor were replaced with a small molecule that either directly activated its expression from the somatic genome or in some way compensated for its activity. To this end, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
605
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 750 publications
(636 citation statements)
references
References 39 publications
25
605
1
5
Order By: Relevance
“…The important role of Sox2 in the second phase of reprogramming is also consistent with the main finding of a recent study that has identified a small molecule (RepSox) able to replace Sox2 for reprogramming [24]. In agreement with our work, this study showed that inhibition of TGF-b signaling is critical to RepSox's replacement of Sox2 in iPSC induction.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The important role of Sox2 in the second phase of reprogramming is also consistent with the main finding of a recent study that has identified a small molecule (RepSox) able to replace Sox2 for reprogramming [24]. In agreement with our work, this study showed that inhibition of TGF-b signaling is critical to RepSox's replacement of Sox2 in iPSC induction.…”
Section: Discussionsupporting
confidence: 92%
“…This unexpected finding was consistent with our hypothesis that a stable intermediate phase between fibroblasts and iPSCs could be achieved through the expression of only three reprogramming factors (Oct4, Klf4, and c-Myc). In fact, similar colonies were present in the original discovery [24,32], although subsequently identified differences in potential for reprogramming set these apart [21][22][23].…”
Section: Confirmation Of Two-phase Ipsc Inductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The treatment with Aza-C or the suppression of the Dnmt1 level induces maturation from partially reprogrammed cells to completely reprogrammed iPS cells. 68), 69) Mesenchymal-to-epithelial transition. During the iPS cell induction from fibroblasts, cells undergo morphological changes that resemble the mesenchymal-to-epithelial Transition (MET).…”
Section: Factors and Pathway Critical For Ips Cell Generationmentioning
confidence: 99%